Pedagogical practices in health promotion: health-related bodily practices for adults and older people - Ferreira, Heidi Jancer [UNESP] (2020)
Background:It is well established in the literature how exercise prevents chronic diseases. Nevertheless, we still lack knowledge about the ways in which health-related bodily practices might contribute to health promotion. Less is known about pedagogies in public health directed at adult and older-age groups, within non-formal educational settings. Considering a lack of tailored and attractive approaches to health-related bodily practices for adults and older people [Pettigrew et al.2019. Encouraging Older People to Engage in Resistance Training: A Multi-Stakeholder Perspective.Ageing & Society39 (8): 1806-1825; Van Dyck, D., L. Mertens, G. Cardon, K. De Cocker, and I. De Bourdeaudhuij. 2017. Opinions Toward PhysicalActivity, Sedentary Behavior, and Interventions to Stimulate Active Living During Early Retirement: Qualitative Study in Recently Retired Adults. Journal of Aging and Physical Activity 25 (2): 277-286], we argue that there is a need to explore pedagogical practices that might further health promotion with this target group. Purpose:Drawing on Antonovsky's theory of salutogenesis [1996. The Salutogenic Model as a Theory to Guide Health Promotion.Health Promotion International11 (1): 11-18], the purpose of the study was to investigate how health and physical education (HPE) professionals delivered health-related bodily practices for adults and older people in community-based programmes. Data collection and analysis:A qualitative and grounded theory study design was employed. Participants included six HPE professionals, three health centre coordinators and thirty-four adults and older people enrolled in four community-based programmes from Brazil. Condensed fieldwork was adopted to generate data through three-days visits to each programme. Multiple data sources comprised semi-structured interviews, non-participant observation of health-related bodily practices sessions and documents/materials produced by participants. Data were analysed through open, axial and selective coding, using the constant comparative method [Charmaz2006.Constructing Grounded Theory: A Practical Guide Through Qualitative Analysis. Book. Vol. 10. London: Sage Publications]. Findings:Three themes were generated to explain the ways HPE professionals worked with adults and older people in health promotion: adopting a holistic view of health, serving as a health resource and nurturing further health resources. These practices included caring attitudes, such as listening carefully to adults and older people, showing attentiveness and responsiveness to them. Moreover, a key finding indicated that the HPE professionals served in their pedagogical practices as health resources, which the adults and older people learned to draw on to cope with life situations and experience health development. Conclusion:The HPE professionals in the four programmes demonstrated they were capable of moving beyond a solely biomedical approach to health and focus on the salutary factors that enable health promotion through the development of a combination of pedagogical practices that were consistent with salutogenesis.